(untitled) (Academia Science Repository, 2023)
Modern technologies have rapidly entered our lives. It is becoming clear that every intellectually developed person cannot imagine his daily life without digital technology and the Internet [1,3,7,9]. Today, when education is becoming more mobile, the doors of great opportunities are opening before every person who wants to learn. Examples include distance learning, online webinars, and seminars [2,4,5]. A new technology that is currently sweeping the education system from one point to another is Telegram bots and channels. Telegram is a cross-platform messenger, that is, it is considered the most convenient program with the function of exchanging media files in various formats [6,8,13].